Coexistence, contacts and conflicts in the precordillera of Tacna during the Late Intermediate Period (AD 1100-1450) - Romuald Housse (Bulletin de l'Institut Français d'Études Andines)
The precordillera of Tacna, between the communities of Sitajara and Tarata, has long had the reputation of being a zone of cohabitation between local, altiplano and coastal populations. However, this scheme, mostly based upon ethnohistorical data, appears to be at odds with several lines of archaeological evidence and with the wider emphases on conflict during the Late Intermediate Period (LIP). In this article, based on the study of the pre-Inca fortified settlements and associated ceramic styles, I outline the modalities of exchange or communication that likely existed between different populations in the area. I also explore the strategies established by the pre-Hispanic populations for the management, the control and defense of the territory.